Composing Research A Contextualist Paradigm for Rhetoric and Composition - Johanek, Cindy (University Press of Colorado, 2000)
Cindy Johanek offers a new perspective on the ideological conflict between qualitative and quantitative research approaches, and the theories of knowledge that inform them. With a paradigm that is sensitive to the context of one's research questions, she argues, scholars can develop less dichotomous forms that invoke the strengths of both research traditions. Context-oriented approaches can lift the narrative from beneath the numbers in an experimental study, for example, or bring the useful clarity of numbers to an ethnographic study. A pragmatic scholar, Johanek moves easily across the boundaries that divide the field, and argues for contextualist theory as a lens through which to view composition research. This approach brings with it a new focus, she writes. "This new focus will call us to attend to the contexts in which rhetorical issues and research issues converge, producing varied forms, many voices, and new knowledge, indeed reconstructing a discipline that will be simultaneously focused on its tasks, its knowledge-makers, and its students." Composing Research is a work full of personal voice and professional commitment and will be a welcome addition to the research methods classroom and to the composition researcher's own bookshelf. 2000 Outstanding Scholarship Award from the International Writing Centers Association.